MURTADHA MUTHAHARI DAN CORAK TEOLOGINYA - Deswita Deswita (Alfuad: Jurnal Sosial Keagamaan, 2018)
Murtadha Muthahari was one of the greatest Muslim philosophers in the 20th century. Muthahari saw philosophy for him only as a tool and method in the practice of thought used to understand religion and as a basis for maintaining it. In this paper, the author tries to discuss Muthahari's thoughts on Tawheed and justice. In his mind, Muthahari always departed from the truth - the truth of religion, to then understand it, interpret it and defend it with philosophical arguments, in the sense that Muthahari was a philosophical theologian.